Artificial Intelligence and Legal Personhood: Ethical, Regulatory, and Accountability Challenges in Contemporary Jurisprudence - Ambuj Sharma (SocioHumania: Journal of Social Humanities Studies, 2026)
This study examines the growing debate surrounding the possibility of granting legal personhood to artificial intelligence (AI) systems within contemporary legal frameworks. As AI technologies become increasingly autonomous in decision-making, innovation, and economic interactions, questions arise concerning accountability, liability, and ethical governance. Using a qualitative library research approach, this study analyzes scholarly literature, legal theories, and global regulatory developments related to AI personhood. The discussion explores historical precedents of non-human legal entities, including corporations and natural objects, and compares them with emerging proposals for electronic legal personality. The findings reveal that while functional legal recognition may offer practical solutions for liability and compensation, current AI systems lack consciousness, moral agency, and intentionality required for full legal personhood. Consequently, most jurisdictions prefer human-centered regulatory models emphasizing transparency, oversight, and institutional accountability. The study concludes that extending legal personhood to AI remains premature and that adaptive governance frameworks are more appropriate for managing future AI-related legal challenges